2021
DOI: 10.1093/mnras/stab1872
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale clustering amongst Fermi blazars; evidence for axis alignments?

Abstract: We find evidence for large-scale clustering amongst Fermi-selected BL Lac objects but not amongst Fermi-selected flat spectrum radio quasars (FSRQs). Using two-point correlation functions, we have investigated the clustering properties of different classes of objects from the Fermi–LAT(Large Area Telescope) 4FGL catalogue. We wanted to test the idea based on optical polarization observations that there might be large volumes of space in which AGN axes are aligned. To do this, we needed a clean sample of blazar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Radio galaxies also showed consistency in their angular momentum (Taylor and Jagannathan 2016), showing large-scale alignment agreement between surveys such as the Faint Images of the Radio Sky at Twenty-centimetres (FIRST) and the TIFR GMRT Sky Survey (TGSS) (Contigiani et al 2017;Panwar et al 2020). Large-scale clustering of Fermi blazars also showed a possible axis alignment (Marcha and Browne 2021). In addition to observational studies, numerical simulations also showed links between the large-scale structure and spin directions (Hahn et al 2007;Zhang et al 2009;Codis et al 2012;Trowland 2013;Libeskind et al 2013Libeskind et al , 2014Forero-Romero et al 2014;López et al 2019).…”
Section: Discussionmentioning
confidence: 55%
“…Radio galaxies also showed consistency in their angular momentum (Taylor and Jagannathan 2016), showing large-scale alignment agreement between surveys such as the Faint Images of the Radio Sky at Twenty-centimetres (FIRST) and the TIFR GMRT Sky Survey (TGSS) (Contigiani et al 2017;Panwar et al 2020). Large-scale clustering of Fermi blazars also showed a possible axis alignment (Marcha and Browne 2021). In addition to observational studies, numerical simulations also showed links between the large-scale structure and spin directions (Hahn et al 2007;Zhang et al 2009;Codis et al 2012;Trowland 2013;Libeskind et al 2013Libeskind et al , 2014Forero-Romero et al 2014;López et al 2019).…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, a large number of studies using numerous different probes show cosmological-scale isotropy and parity violations, suggesting that the Cosmological Principle might not be aligned with observations (Aluri et al, 2023). In addition to the cosmic microwave background radiation (Lue et al, 1999;Eriksen et al, 2004;Abramo et al, 2006;Cline et al, 2003;Gordon and Hu, 2004;Land and Magueijo, 2005;Campanelli et al, 2007;Mariano and Perivolaropoulos, 2013;Ade et al, 2014;Zhe et al, 2015;Santos et al, 2015;Dong et al, 2015;Gruppuso et al, 2018;Ashtekar et al, 2021;Luongo et al, 2022;Yeung and Chu, 2022), such probes also include dark energy (Adhav et al, 2011;Adhav, 2011;Perivolaropoulos, 2014; Colin * lshamir@mtu.edu et al, 2019), H o anisotropy (Luongo et al, 2021;Dainotti et al, 2022), distribution of galaxy morphology types (Javanmardi and Kroupa, 2017), cosmic rays (Aab et al, 2017), quasars (Hutsemékers et al, 2014;Slagter, 2022;Secrest et al, 2020;Zhao and Xia, 2021;Secrest et al, 2021), LX-T scaling (Migkas et al, 2020), Ia supernova (Javanmardi et al, 2015;Lin et al, 2016), short gamma ray bursts (Mészáros, 2019), large-scale clustering of Fermi blazars (Marcha and Browne, 2021), radio galaxies…”
Section: Introductionmentioning
confidence: 78%
“…1 See also: Christian (2020) 2 See also: Nadathur (2013); Marinello et al (2016); Hutsemékers et al (2014) 3 See also : Marchã & Browne (2021) (rest equivalent widths 𝑊 𝑟 ,2796 , 𝑊 𝑟 ,2803 ) arising in the haloes corresponds to the properties of the galaxy and galaxy clusters, although there is still uncertainty about the relative importance of morphology, luminosity, impact parameter, galaxy inclination etc., and combinations of these, that lead to the different classes (weak, strong) of absorbers. See for example: Lanzetta & Bowen (1990); Churchill et al (2000); Steidel et al (2002); Churchill et al (2005); Chen et al (2010); Bordoloi et al (2011).…”
Section: The Mg II Approachmentioning
confidence: 99%